Seed Hardening: A Way to Tolerate Against Abiotic Stress in Rainfed Areas - Jain, Lokesh Kumar; Verma, Mahendra Prakash; Ram, Nema; Choudhary, Anirudh; Parewa, Hanuman Prasad (International Journal of Economic Plants, 2022)
Pre-sowing hardening or priming of seeds is one of the best methods for altering the biochemical and physiological process of seeds for favourable condition to induce drought tolerance in emerging seedlings. The recurrent phenomenon in rainfed areas i.e. soil moisture stress immediately after sowing affects seeds germination and their establishment. Under sub-optimal environmental conditions like rainfed farming, poor seed germination followed by poor field establishment is a common phenomenon. Seed hardening enables seedlings to survive this early moisture stress. hydration of seeds for short term before planting greatly benefits stand establishment along with the uses of chemicals like potassium or sodium phosphate would give additional advantage. It is defined as the process of soaking seeds in chemical solution for specified time and then drying to induce tolerance to drought. Various seed priming/hardening techniques have been developed including hydro-priming, halo-priming, osmo-priming and hormonal priming. Micronutrient seed treatments, which include seed priming and seed coating, are an attractive and easy alternative. Seed hardening promotes early establishment provides more strengthen to plant and it became competitive against infections and diseases is related to gene regulation and expression under stress conditions. The discovery of plant hormones in the 1920s underlined the crucial role of these compounds in seed desiccation tolerance, reserve mobilization, as well as cell division and cell elongation occurring during germination. The seed hardening is considered as low cost technology and is the most important requirement for pre-monsoon sowing. Seed hardening offer an attractive option for resource poor farmers. During seed hardening, seeds are subjected to partial hydration followed by dehydration before sowing.